Transformasi Tata Kelola Digital: Tantangan dan Peluang bagi Pemerintah Daerah di Era Society 5.0 - Sri Yulianty Mozin; Hardiyanto Hardiyanto; Syarifah Arkani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The rapid advancement of digital technology has fundamentally altered the landscape of public governance, compelling local governments to adapt and embrace digital transformation. This study investigates the challenges and opportunities faced by local governments in Indonesia in implementing digital governance transformation within the framework of Society 5.0. Using a systematic literature review and case study methodology, this research analyzes governance transformation policies, institutional readiness, digital infrastructure, and human resource capacity across selected Indonesian regional governments. The findings reveal that while significant opportunities exist including enhanced public service delivery, improved transparency, citizen participation, and inter-agency coordination substantial challenges persist in digital infrastructure disparities, limited human resource capacity, regulatory ambiguity, and cybersecurity vulnerabilities. The study identifies five critical success factors for effective digital governance transformation: strong political commitment, adequate digital infrastructure investment, comprehensive human resource development, adaptive regulatory frameworks, and inclusive citizen engagement mechanisms. This research contributes to the theoretical discourse on e-government and digital governance in the context of developing countries, while offering practical policy recommendations for local governments navigating the transition to Society 5.0. The implications extend to policymakers, practitioners, and scholars engaged in public administration reform in the digital age.